The effect of multilingual glossaries of meta-cognitive verbs on improving assessment performance: a case study at a South African university of technology - Van Stryp, Jackie Etta (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.